New micromechanics model for saturated porous media with connected pores - Jia, C. L.; Chen, Y. Q.; Huang, Z. P. (Archive of Applied Mechanics, 2016)
A new micromechanics method is proposed to investigate the effective properties of saturated porous media with connected pores. This topic is seldom discussed in the literature because it is difficult to describe the connected pores and skeleton using conventional micromechanics methods. A new micromechanics model (i.e., Model I) is suggested to characterize such saturated porous media in which the pores saturated by fluid are taken as the matrix, and the interconnected randomly oriented long fiber (ROLF)-like solid skeleton is taken as the inclusions. The proposed model is verified by numerical simulations; the simulation results indicate that the difference of the elastic constants calculated for media with interconnected pores and for those with dispersed ROLF solid inclusions is small. Thus, the elastic moduli of Model I can be treated as approximate values for porous media with connected pores. Further, a modified Eshelby tensor for spherical inclusions is derived based on the equivalency of the elastic moduli of Model I and a conventional micromechanics model in which spherical fluid inclusions are distributed randomly in a solid matrix. By means of the modified Eshelby tenor, conventional micromechanics methods can be utilized directly to calculate the effective mechanical and thermal properties of saturated porous media with interconnected pores. Some examples are presented to show that the macroscopic elastic moduli predicted by the proposed method are in good agreement with test data found in the literature.
Keywords: conductivity; connected pores; effective constants; effective elastic properties; effective properties; interpenetrating phase composites; mechanical-behavior; micro; micromechanics model; modified eshelby tensor; poroelastic materials; porosity; rocks; saturated porous media; variational approach